Electrochemical behaviour of tocopherols: possibilities of their simultaneous voltammetric detection - Jashari, Granit; Kastrati, Gylxhane; Korecká, Lucie; Metelka, Radovan; Sýs, Milan; Ashrafi, Amirmansoor (My University, 2021)
An electroanalytical study for possible simultaneous detection of three naturally occurring isomers of vitamin E (α, γ, and δ-tocopherol) was performed. This research includes several optimization steps, such as selection of electrode material, composition of working medium, selection of electrochemical technique, and parameters of square-wave voltammetry (SWV), to reach a well-defined recognition of peaks. A glassy carbon electrode, 99.9% acetonitrile containing 0.1 mol L−1 lithium perchlorate, SWV at the potential step of 1 mV, potential amplitude of 25 mV, and frequency of 25 Hz were decided as the most suitable working conditions. Nevertheless, the corresponding anodic peaks were not sufficiently separated due to their overlapping. Thus, four standard evaluation methods (polynomial or linear baseline, zero base, and deconvolution) were compared, and the last-mentioned method was chosen as optimum. Similar linear ranges from 3.0 × 10−6 to 1.0 × 10−5 mol L−1 were obtained for α, γ, and δ-tocopherol, characterized by determination coefficient of 0.998, 0.985, and 0.994, quantification limits of 11.28, 2.70, and 3.67 × 10−6 mol L−1 and detection limits of 3.72, 0.89, and 1.21 × 10−6 mol L−1, respectively. A recovery from 72.0 to 128.5% for different concetration ratios of tocopherols has been achieved. This recovery range is in the accordance with values reported for liquid chromatography.
Elektrochemické chování tokoferolů: možnosti jejich simultánní voltametrické detekce
Keywords: evaluation methods; glassy carbon electrode; simultaneous detection; square wave voltammetry; tocopherols; metody hodnocení; elektroda ze skelného uhlíku; simultánní detekce; square-wave voltametrie; tokoferoly